The model of character teacher: Phenomenology at Daruttaqwa Gresik Islamic Boarding School - Muhammad Anas Ma'arif; Muhammad Husnur Rofiq (ATTARBIYAH: Journal of Islamic Culture and Education, 2018)
The importance of shaping the character of children in order to carry out ethical values consciously and sincerely becomes a separate problem for all educators. Educator's personality is needed so that children can imitate the ways of educators in carrying out various daily activities. Set an example is one powerful way to give children an example and do good so that it becomes a character or an intact character. Children prefer to be given examples of behavioral examples directly rather than just giving orders. Purposes-This study aims to describe patterns of character educator models with Amali Sufism bases. Design/methodology /approach- This study uses a qualitative approach to the type of phenomenology which captures the behavior of educators who experience and teach exemplary behavior at the Daruttaqwa Islamic Boarding School. Findings- Exemplary actions taken by educators in Pesantren Daruttaqwa through attitudes, thoughts and behaviors that are consistently based on religious values such as, ikhlas, tawaduk, zuhud, destiny for teachers, loving teachers and piety to Allah.  Originality- Sufism-based modeling ranging from thinking, attitudes and behavior exemplified externally and internally both (spontaneously directly) or indirectly exemplified by educators with habituation strategies.